Prefractionation of LiCl from concentrated seawater/salt lake brines by electrodialysis with monovalent selective ion exchange membranes. (20th August 2018) - Guo, Zhi-Yuan; Ji, Zhi-Yong; Chen, Qing-Bai; Liu, Jie; Zhao, Ying-Ying; Li, Fei; Liu, Zhi-Yong; Yuan, Jun-Sheng
Abstract: Exploring the lithium resources in concentrated seawater/salt lake brine could provide necessary support for the sustainable development in future. Selective-electrodialysis (S-ED, equipped with monovalent selective ion-exchange membranes) is considered as an effective way to reduce the ratio of magnesium to lithium in concentrated seawater/salt lake brines. However, the effectiveness of the prefractionation of lithium chloride from brine is not clearly investigated, because both seawater and salt lake brines are complex mixtures. Nowadays, only simple systems with binary or ternary cations system have been investigated. Based on a clean production process for the utilization of concentrated seawater/salt lake brine, the prefractionation of LiCl from concentrated seawater/salt lake brines by S-ED was investigated in this work. From the concentrated seawater experiments, it is beneficial to improve the RLi (recovery ratio of Li + ) at a higher voltage, but an excessively high working voltage is adverse to the preliminary separation between Li + and Mg 2+ ; a bigger VC /VD (initial volume ratio of concentrating and desalting solution, VD  = 2.5 L in this paper) is favorable to increase RLi and reduce ESEC (specific energy consumption of Li + ). At the optimal voltage of 7 V and VC /VD of 0.6, the mole ratio of LiCl: MgCl2 : MgSO4 increased from 1: 2.227: 2.463 to 1: 1.461: 0.085. For the salt lake brines, the optimal voltage for the LiCl prefractionation in the selected brine system was 10 V, which had a higher RLi of 76.45% and an appropriate ESEC of 0.66 kWh/(mol Li). Finally, the parameters of RLi, ESEC and separation effect of LiCl were discussed for the salt lakes of West Taijinar, East Taijinar and Yiliping in China. It is found that the East Taijinar salt lake brine was more suitable to obtain LiCl at a lower ESEC . Graphical abstract: Prefractionation of LiCl from concentrated seawater/salt lake brines by selective-electrodialysis (S-ED). Image Highlights: LiCl's prefractionation could be implemented by selective-electrodialysis (S-ED). S-ED could increase LiCl: MgCl2 : MgSO4 to 1: 1.461: 0.085 for concentrated seawater. The order of LiCl extraction efficiency was East Taijinar > Yiliping > West Taijinar. LiCl: MgCl2 : MgSO4 increased to 1: 1.089: 0.199 with S-ED for East Taijinar brine.